Effects of dynamic vulcanization and acrylic acid on properties of recycled poly(vinyl chloride)/acrylonitrile butadiene rubber (PVCr/NBR) blends - Supri, A. Ghani; Hanafi, A. Ismail; Yusof, A. M M (Taylor & Francis, 2009)
Link to publisher's homepage at http://www.informaworld.com/smpp